"Assessment of Microbial Indicator Loads and Salmonella spp. prevalence using MicroTally on Beef Carcasses in a Commercial Processing Facility - Paz M., Nadia I. (Zamorano: Escuela Agrícola Panamericana, 2025)
This study aimed to research the microbial contamination on beef carcasses in a commercial processing facility using two MicroTally® Mitt procedures for sampling. The primary objective was to evaluate the microbial loads of aerobic counts (AC), Enterobacteriaceae (EB), and Escherichia coli (EC) at various processing stages and compare the effectiveness of dry versus pre-moist sampling methods. Samples were collected from different carcass parts, at different stages and locations including the hide, pre-evisceration, post-evisceration, cold carcass, chuck, trim, and final rail. For the microbial analysis, the TEMPO® system was used for enumeration. The results demonstrated variations in microbial loads across different processing stages and sampling methods. Post-evisceration premoisten bacteria load is significantly difference (P < 0.05) from the dry sampling method for AC, EB, and EC. Moreover, no significant was shown between the treatments in the other stages and locations. However, a significant interaction between treatments and areas was found on AC and EC, indicating that effectiveness varied depending on the area. The investigation demonstrates the presence of the microorganisms at different sample points during the processing line by using MicroTally® Mitt. The findings contribute to improved microbial monitoring and management practices in beef processing facilities to ensure food safety and quality.